Topological K-equivalence of analytic function-germs - Alvarez, Sergio; Birbrair, Lev; Ferreira Costa, Joao Carlos [UNESP]; Fernandes, Alexandre (Versita, 2010)
We study the topological K-equivalence of function-germs (a"e (n) , 0) -> (a"e, 0). We present some special classes of piece-wise linear functions and prove that they are normal forms for equivalence classes with respect to topological K-equivalence for definable functions-germs. For the case n = 2 we present polynomial models for analytic function-germs.
Keywords: Topological K-equivalence; Topological equivalence; Function-germs